High Performance Liquid Chromatographic Determination ofInactive Carboxylic Acid Metabolite of Clopidogrel in HumanSerum: Application to a Bioequivalence Study - Golbarg Ghiasi,; Amir Farshchi,; Gholamreza Bahrami, (Iranian Journal of Pharmaceutical Sciences, 2009)
A sensitive and rapid method is described for determination of clopidogrel carboxylic acid (CCA), the inactive metabolite of the antiplatelet agent clopidogrel in human serum. The analytical procedure involves liquid-liquid extraction of the analyte and an internal standard (phenytoin) with ethyl acetate. Amobile phase consisting of 0.05 M phosphate buffer containing triethylamine (0.5 ml/l; pH 5.7)and acetonitrile (56:44; v/v) was used and chromatographic separation was achieved using a C18analytical column at detector wavelength of 220 nm. The calibration curves were linear over a concentration range of 0.05-10 μg/ml of CCAin human serum. The total run time of analysis was 5.5 min. and the lower limits of detection (LOD) and quantification (LOQ) were 0.02 and 0.05 μg/ml, respectively. The method validation was carried out in terms of specificity, sensitivity, linearity,precision, accuracy and stability. The validated method was applied in a randomized cross-over bioequivalence study of two different clopidogrel preparations in 24 healthy volunteers.